Preparation of Starch/Gelatin Blend Microparticles by a Water-in-Oil Emulsion Method for Controlled Release Drug Delivery - Theeraphol Phromsopha; Yodthong Baimark (International Journal of Biomaterials)
Information on the preparation and properties of starch/gelatin blend microparticles with and without crosslinking for drug delivery is presented. The blend microparticles were prepared by the water-in-oil emulsion solvent diffusion method. Glutaraldehyde and methylene blue were used as the crosslinker and the water-soluble drug model, respectively. The blend microparticles were characterized by scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, and UV-Vis spectroscopy. The functional groups of the starch and gelatin blend matrices were determined from the FTIR spectra. Blend microparticles with a nearly spherical shape and internal porous structure were observed from SEM images. The average particle size of the gelatin microparticles depended on the crosslinker ratio but not on the starch/gelatin blend ratio. The in vitro drug release content significantly decreased as the crosslinker ratio increased and the starch blend ratio decreased. The results demonstrated that the starch/gelatin blend microparticles should be a useful controlled release delivery carrier for water-soluble drugs.